Ulysse à la dérive : de déviations en faux-fuyants, un itinéraire élisabéthain - Charlotte Coffin (Revue LISA)
From Antiquity onwards, the Ulysses myth has been subject to contradictory interpretations, depending on whether his cunning intelligence is seen to indicate wisdom or deceitfulness, and whether the stress is laid on the Greek’s sly speeches or on his painful travels. Yet Elizabethan texts paradoxically deviate from this rich tradition as they often present a much simpler version of the hero, where the phrase “wise Ulysses” excludes any attempt at critical investigation. This article offers a survey of a variety of texts and genres, in order to show how both allegorical interpretations and rhetorical exploitations of the myth tend to erase ambivalence, whereas Shakespeare’s Troilus and Cressida fully explores its suggestions of  the dangerous power of eloquence.